Avaliação comportamental e neuroquímica de ratos em dessincronização forçada: possíveis implicações para um modelo animal de oscilações no humor - Koike, Bruna Del Vechio (2013)
Bipolar disorder has been growing in several countries. It is a disease with high mortality and has been responsible by the social isolation of the patients. Bipolar patients have alterations in circadian timing system, showing a phase shift in various physiological variables. There are several arguments demonstrating alterations in circadian rhythms may be part of the bipolar disorder pathophysiology. Given the necessity for further elucidation, the goal of this study was to validate the forced desynchronization protocol as an animal model for bipolar disorder. To do this, Wistar rats were submitted to a forced desynchronization protocol which consists in a symmetrical light dark cycle with 22h. Under this protocol, rats dissociate the locomotor activity rhythm into two components: one synchronized to the light / dark cycle with 22h, and another component with period longer than 24 hours following the animal endogenous period. These rhythms with different periods sometimes there is coincidence, which we named CAP (Coincidence Active Phase) and the opposite phase, non-coincidence, called NCAP (Non-Concidence Active Phase). The hypothesis is that in CAP animals present a mania-like behavior and animals in NCAP depressive-like behavior. We found some evidence described in detail throughout this thesis. In sum, the animals under forced desynchronization protocol were more stressed, showed an increase in stereotypic behaviors such as grooming and reduction in other behaviors such as risk assessment and vertical exploration when compared to the control group. The CAP animals showed increased locomotor activity, especially during the dark phase when compared to controls (rats under T24) and less depressive behavior in the forced swim test. The animals in NCAP showed a higher anxiety in elevated plus maze, but they don t have ahnedonia. The animals under dissociation have more labeled 5HT1A cells at the amygdala area, which appoint that they have more amygdala inhibition. Taking these data together, we could partially validated the forced desynchronization protocol as an animal model for mood oscillations